Perbandingan Manajemen Kurikulum Sebelum Dan Selama Pandemi Covid-19 Di Sekolah Dasar Islam Mohammad Hatta - Nur Maulidiyah (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2021)
The curriculum is the core subject of education. Oliva mentioned "curriculum that is thought" (what), in the form of programs, plans, materials to be taught (content). Meanwhile, the meaning of learning (instruction) is more of "means used to teach that which is thought" (how), in the form of methods, teaching strategies, teaching approaches, implementation of learning in class and outside the classroom. Once the importance of curriculum management as the main management substance in schools, the basic principles of curriculum management emphasize that the learning process can run well, by measuring the achievement of goals by students and encouraging teachers to develop and continuously perfect learning strategies carried out in class.The curriculum plays an important role in realizing quality and quality schools, to create a quality curriculum, empowerment in curriculum management is needed. Management of the institutional-level curriculum needs to be coordinated by the leadership which is developed integrally in the context of School-Based Management and the Education Unit Level Curriculum and is adjusted to the vision and mission of the Educational Institution. The SDI Mohammad Hatta curriculum is intended for all school members, especially students, educators and education personnel, the formation of school culture can be carried out by schools through a series of planning activities, implementation of learning that is more student-oriented, comprehensive assessment of school-level planning in essence is strengthening the preparation at SDI Mohammad Hatta level, such as establishing a vision, mission, goals, curriculum structure, academy calendar and syllabus preparation. This type of qualitative research uses descriptive research methods. The purpose of this study was to describe the curriculum management at SDI Mohammad Hatta and to describe how the education unit level curriculum was before and during the Covid-19 pandemic.